Health, Rights and Dignity Philosophical Reflections on an Alleged Human Right - Erk, Christian (De Gruyter, 2010)
The idea that there is such a thing as a human right to health has become pervasive. It has not only been acknowledged by a variety of international law documents and thus entered the political realm but is also defended in academic circles. Yet, despite its prominence the human right to health remains something of a mystery - especially with respect to its philosophical underpinnings. Addressing this unfortunate and intellectually dangerous insufficiency, this book critically assesses the stipulation that health is a human right which - as international law holds - derives from the inherent dignity of the human person. Scrutinising the concepts underlying this stipulation (health, rights, dignity), it shall conclude that such right cannot be upheld from a philosophical perspective.